Os sujeitos docentes e a qualidade da educação básica: indicadores de rendimento escolar da rede pública municipal e estadual de Cascavel no Paraná - Assis, Lidia Maria Lopes (2018)
In this research, we seek to examine the current educational indicators used to verify the quality of basic education in Brazil, focusing mainly on the Basic Education Development Index (IDEB) and the International Student Assessment Program (PISA). We intended to verify, from the perspective of the teaching subjects, whether these indicators, besides the quantitative diagnosis, induce the adoption of policies for the effective improvement of basic education in municipal and state public school networks in the city of Cascavel, Paraná, in the period of 2010 to 2016. In order to understand the centrality of this large-scale evaluation from the 1990s, we performed a brief retrospective of the educational reforms implemented at that time, as well as consider the definition of the categories of evaluation and school performance and the categories of school performance and educational quality to assist in the interpretation of data analysis. We also believe it is necessary to reflect on the current National Education Plan (PNE) Law 13.005/2014, PISA and IDEB, due to the discourse that the three are configured as guiding educational policies for educational quality. Thus, we collect data to verify, from the teaching subjects, whether the quality of public basic education measured by the IDEB is reflected in the working conditions of the teachers and the quality of student care in the municipality of Cascavel, Paraná. We conclude that, by the way in which the large scale evaluation is carried out, the results expressed by the indicators prove to be insufficient to reveal the quality of basic education, since in some moments the indexes can point to numerical advances without the full realization taking place of learning.